Perceived Value, Emotional Bonds, and Pop Culture: Drivers of Brand Loyalty - Pratama, Muhammad Rizky Andhika; Puspaningrum, Astrid; Prabandari, Sri Palupi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The global fast fashion industry, including brands like Uniqlo, faces increasing challenges in maintaining brand loyalty amid fierce competition and evolving consumer behavior. This study explores the effect of perceived value on brand loyalty among Uniqlo customers in Jakarta, with brand love and brand trust as mediators, and pop culture involvement as a moderator. Using a quantitative, explanatory approach grounded in Relationship Marketing Theory, data were gathered from 232 respondents through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that perceived value does not directly impact brand loyalty. Instead, it significantly influences brand love and brand trust, which fully mediates the relationship highlighting the importance of emotional connection and trust in fostering loyalty. Meanwhile, pop culture involvement does not significantly moderate the link between perceived value and loyalty, suggesting that trend-based marketing alone is insufficient to build sustained loyalty. These results emphasize that fast fashion brands must go beyond product value or trend alignment, focusing instead on nurturing emotional bonds and customer trust to drive long-term loyalty. This study offers valuable insights for brand managers seeking to strengthen consumer relationships in an increasingly competitive fashion landscape.